Insights Into Spatial Orientation and Cognition in Tarantulas (Araneae: Theraphosidae) Under Natural Conditions, With Notes on Possible Ontogenetic Niche Shifts - Zamani, Alireza; West, Rick C. (Wiley, 2026)
Research on cognition in spiders, particularly in relation to navigation, has primarily focused on araneomorphs studied under controlled conditions. Mygalomorphs, such as tarantulas (Theraphosidae), have been largely neglected and almost nothing is known about their cognitive foraging behaviour in natural environments. Here, we present nine observations of arboreal and fossorial New World tarantulas, including a blind cave-dwelling species, which together provide rare field-based evidence that tarantulas may be capable of flexible, experience-based navigation. All observed arboreal species, as well as two fossorial species, exhibited behaviour that may reflect spatial learning, by foraging in prey-rich locations situated relatively far from their retreats. This behaviour differs from ontogenetic shifts in habitat use, which are noted here in several species for comparison; possible ontogenetic shifts in foraging behaviour in troglobitic tarantulas are also briefly discussed. The remaining observations involve tarantulas responding to disturbance with fast, direct returns to their burrows without disorientation. We discuss the likely allothetic and idiothetic cues underlying these behaviours, while also considering alternative or complementary explanations for retreat recognition and foraging movements based on chemical and chemo-tactile cues. Finally, we briefly review existing experimental research on tarantula cognition, as well as studies on physiological and behavioural changes associated with stress or altered internal states that may interact with cognitive processes.